Identifikasi Efektivitas Lichen Crustose sp. (Cryptochemia) dan Lichen Foliose sp. (Parmelia) Sebagai Bioindikator Tingkat Pencemaran Udara - Nisa, Alyyah Fikrotun; Rosdiana, Laily; Roqobih, Fikky Dian (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2024)
Air pollution is still an environmental problem that has not been resolved until now. There are several alternative methods that can be applied to monitor air quality levels, one of which is using bioindicators. Lichens can be used as bioindicators because they are accumulators and are very adaptive to changes in environmental conditions. This study aims to assess the effectiveness of Crustose sp. (Cryptochemua) and Foliose sp. (Parmelia) lichens as bioindicators of air pollution levels. This study used a systematic review method. Literature was selected based on 3 criteria: relevant to the topic, journal articles within 5 years, and from SCOPUS or SINTA accredited journals. After the selection process, 6 articles were selected for review based on the specified criteria. The results showed that to identify Crustose sp. (Cryptochemua) and Foliose sp. (Parmelia) lichens as bioindicators of air pollution, it is not enough to only consider the number of lichens or morphology found. However, it is also necessary to identify the affected lichen species, biotic and abiotic factors in order to obtain effective and valid results. For future researchers, it is recommended to compare the efficiency of Crustose sp. and Foliose sp. lichen plants as bioindicators of air pollution with other plants.